Global research trends in partograph: A bibliometric analysis - Dhiya An, Alfun; Maulidya, Asri Nur; Ulfa, Maria (Universitas Airlangga, 2025)
HIGHLIGHTS This study highlights growing global attention on the partograph as a part of labor monitoring. Partograph use remains inconsistent and affects clinical decision-making and management of labor. Future studies should focus on digital monitoring and policy effectiveness in intrapartum care as a part of enhancing maternal and neonatal outcomes. ABSTRACT Objective: The present study aimed to clarify the emerging patterns in partograph utilization, its development, and its impact on clinical practice. Materials and Methods: A bibliometric analysis was conducted using Scopus as the primary database. Articles were retrieved using the keywords “Partograph” or “Partogram” and analyzed using two strategies: performance analysis (Scopus “analyze” function) and network analysis (VOSviewer and NVivo). Results: Five hundred and thirteen articles published between 1965 and 2025 were analyzed. Performance analysis revealed that the most cited studies focused on labor management, labor progression, and maternal and neonatal health outcomes. The leading publishing countries included Ethiopia, the United States, the United Kingdom, India, and South Africa. Network analysis identified strong connections between partograph research and healthcare quality, personnel delivery, and facilities. Research trends evolved from early studies on spontaneous delivery, dystocia, and maternal mortality to more recent investigations into partograph utilization as a healthcare service quality improvement tool. Pearson correlation analysis showed strong associations between partograph use and birth outcomes (0.81), mortality (0.78), and healthcare workers’ perspectives (0.76). Conclusion: Research on partograph utilization continues to expand, focusing on labor monitoring and its impact on maternal and neonatal outcomes. Recently, studies have shifted toward labor-management quality, healthcare service improvement, and patient safety. However, certain areas remain underexplored, presenting opportunities for further research.